Transcriptome Profiling of Different State Callus Induced from Immature Embryo in Maize - Kaiwu zhang; Dengxiang Du; Wei Wang (Journal of Chemistry)
Embryogenic and regenerable tissue cultures are widely used in plant transformation. To dissect the molecular mechanism of embryogenesis, we used inbred line A188 as the material; the immature embryo of kernels (15 day after pollination, 15DAP) was isolated and cultured in inducing medium and subjected to RNA-Seq. The results revealed that 5,076 differentially expressed genes (DEGs) were involved in morphological and histological changes and endogenous indole-3-acetic acid (IAA) alteration. Functional analysis showed that the DEGs were related to metabolic pathways and biosynthesis of secondary metabolites. In particular, ARF16 and ARF8 genes of auxin response factors (ARF) were upregulated from EC to IDC and EC to IRC. Meanwhile, BBM2, SERK1, and SERK2 genes of the embryogenic pathway were upregulated, and WIP2 and ESR genes of the wound-inducible were upregulated from EC to IDC and EC to IRC. These changes can improve conversion efficiency from EC to IRC, which is important for elucidating the underlying molecular mechanisms of callus formation.